A Hawkes model of the transmission of European sovereign default risk - Ana-Maria Dumitru; Tom Holden (ZBW - Leibniz Information Centre for Economics; ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2017)
The run-up to the Greek default featured marked increases in the cost of insuring sovereign debt from almost all European countries. One explanation is that market participants believed a default in one country might increase the risk of a future default in another, and so news about one country could impact all others. To test for such dynamic contagion between credit related events in different countries, we develop a procedure for tractably estimating high-dimensional Hawkes models using credit default swap prices. Unlike the prior literature, we are able to perform this estimation via maximum likelihood, even without observing events. We escape the curse of dimensionality by modelling a market portfolio of risk across countries. We find significant spillovers in credit risk between countries, with Spain, Portugal and Greece driving events in the other countries considered.
Keywords: C58; G12; 330; sovereign CDS spreads; credit risk; multivariate self-exciting point process; systemic risk